The Role of Endorsers in Optimizing Sme Promotion Through Instagram Social Media in Palembang - Aquina, Salsa Melania Aquina; Zinaida, Rahma Santhi; Helmi, Sulaiman; Jabir, Bastian (Indonesian Scientific Publication, 2024)
The advancement of information technology and the growing popularity of e-commerce have revolutionized marketing culture, allowing producers to connect directly with consumers through platforms like Instagram, regardless of time and location. This study, titled